KNOWLEDGE PRACTICE GAPS ABOUT NEEDLE STICK INJURIES AMONG HEALTHCARE WORKERS AT TERTIARY CARE HOSPITALS OF PAKISTAN - Kumar, Ameet; Khuwaja, Ali Khan; Khuwaja, Amin Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: The aim of our study were to assess the knowledge and practice gaps about Needle Stick Injuries (NSIs) and their associated factors among Health Care Workers’ (HCWs) at tertiary care hospitals of Pakistan. Methods: A cross-sectional study was conducted in two tertiary care teaching hospitals in Karachi, Pakistan, representing both private and public health sector. During the months of January to May 2008, trained medical graduates interviewed 497 HCWs (Doctors and Nurses) who were working in those particular hospitals for more than a year and were willing to participate in the study. Results: Overall the knowledge about transmission of HBV HCV and HIV was good. However, 19.1 and 12.3% HCWs had misconception about the transmission of malaria and tuberculosis by NSIs; more female and working as a nurse. Furthermore, a large number of participants had lack of knowledge for the transmission of infectious mononucleosis. Over two third of study subjects were not vaccinated for hepatitis B infection, again more females (p=0.002) and nurses (p<0.001). Large numbers of study participants were not wearing protective cloths, and do not us sharp containers. Similarly, preponderance of study subjects does not avoid breaking needle by hands and leave syringes open; these poor practices are significantly more prevalent among those working for more than five years and doctors (p=0.003). Conclusion: In addition to lack of knowledge, poor practices were reported in this study. Proper curriculum reform and training are required to protect the health Care workers and patients. Further research and interventions are suggested in this regards. Keywords: knowledge, practice, public and private sector, Pakistan.